Consumers' awareness, acceptance and attitudes towards functional foods in Turkey. (2nd September 2014) - Büyükkaragöz, Aylin; Bas, Murat; Sağlam, Duygu; Cengiz, Şaziye Ecem
Abstract The aim of the present study was to investigate consumers' awareness, acceptance and attitudes towards functional foods in Turkey. Eight hundred and eight people participated in this study: aged between 20 and 80 years, 38.5% were male and 61.5% were female. Participants were given a questionnaire and were asked to fill it in by themselves to minimize the influence of the interviewer. Results indicated that socio‐demographic characteristics such as age, education level and income level are important indicators of consumers' awareness and consumption of functional food. The results show that the female respondents were 2.987 times more aware of functional food than the male respondents. Similarly, the likelihood of respondents having awareness of functional food was 1.431 times greater among those who had a higher educational level than among those with a lower educational level. Consumers who used vitamin supplements were 1.228 times more aware of functional food than other consumers. The results show that older respondents were 3.395 times more aware of functional food than younger respondents. Respondents with a history of familial diseases were more likely than others to have consumed margarine with plant sterol, fruit juices fortified with vitamin C, and breakfast cereals fortified with vitamins and minerals. Those with a diet‐related problem were more likely to have consumed cholesterol‐lowering products than those without a problem. As a conclusion, this study has shown that socio‐demographic characteristics such as age, education and income levels, and prices are important indicators that influence consumers' awareness and consumption of functional food. These results suggest that this type of knowledge could affect consumers' interest in functional foods, and therefore educational strategies might be necessary to encourage the consumption of functional foods.